Comparison of passive haemagglutination and enzyme-linked immunosorbent assay for serodiagnosis of plague - Williams, James E. (1982)
Sera of 42 suspect plague cases from Ovamboland, Namibia, were examined. ELISA proved more sensitive than passive haemagglutination for the detection of F1 antibody and increased positive serodiagnoses of plague by 7-42%.